Chapter 4. The places of Franz Josef Land: current visits and imagery - Umbreit, Andreas (Septentrio Conference Series, 2015)
Recent tourist cruises of Franz Josef Land have offered the chance to search for the remains of historic expeditions to the islands, as well as expeditions that used the islands as a base from which to try to reach the geographic North Pole. Expedition leader Andreas Umbreit discusses his recent such finds at both Greely Island and Teplitz Bay on Rudolf Island, as well as several other sites.